2014
DOI: 10.1039/c4mb00459k
|View full text |Cite
|
Sign up to set email alerts
|

Role of a remote leucine residue in the catalytic function of polyol dehydrogenase

Abstract: Studies on the protein-metal binding sites have mainly focused on the residues immediately surrounding the reacting substrate, cofactors, and metal ions. The contribution of residues in remote layers to the highly optimized microenvironments of catalytic active sites is not well understood. To improve our understanding, the present study examined the role of remote residues on the structure and function of zinc-dependent polyol dehydrogenases. We used an integrated computational and biochemical approach to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…The effect of second shell residues on binding affinity and kinetics in protein‐ligand interactions is poorly documented. Several groups have reported observations similar to ours [25–28] . One study described a role for the remote residue Phe46 in myoglobin on ligand binding [25] .…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…The effect of second shell residues on binding affinity and kinetics in protein‐ligand interactions is poorly documented. Several groups have reported observations similar to ours [25–28] . One study described a role for the remote residue Phe46 in myoglobin on ligand binding [25] .…”
Section: Resultssupporting
confidence: 72%
“…One study described a role for the remote residue Phe46 in myoglobin on ligand binding [25] . Another highlighted the role of the second shell in protein‐metal recognition [27] . Specifically, a study of zinc finger structures demonstrated the significance of second layer packing in shielding the negatively charged zinc finger cores.…”
Section: Resultsmentioning
confidence: 99%
“…The loss of VA affinity, in the case of some mutants, was correctly predicted by the ΔE calculations. Similar studies supplied evidence that substrate binding differences affect the enzyme catalysis [45]. Therefore, the SQM methodology enabled us to explain the experimental results obtained with the different LiP variants.…”
Section: Resultsmentioning
confidence: 62%
“…This destabilizes the interaction between residues in AgaA‐E147S/D271A and agaro‐octaose hence binding more loosely in agreement with the decreased affinity determined by SPR (Table ). In previous studies, focusing on H‐bond forming ability, it was suggested that perturbed H‐bonds may affect substrate binding affinities, turnover, and the kinetically preferred reaction pathway . Therefore, it is not surprising that loss of H‐bond network interactions by the single point mutation D271A impairs binding affinity.…”
Section: Resultsmentioning
confidence: 99%